Keabsahan Hukum Perjanjian Jual Beli melalui Whatsapp Bisnis berdasarkan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Alfatunisah, Alfatunisah; Sativa, Annisa (Legal Standing : Jurnal Ilmu Hukum, 2025)
The rise of digital technology has driven business actors to use WhatsApp Business as a platform for buying and selling transactions, which in turn increases the risk of breach of contract (wanprestasi) against consumers. This study aims to identify the causes of business actors' breach of contract through WhatsApp Business, analyze legal protection for consumers based on Law Number 8 of 1999 on Consumer Protection (UUPK), and evaluate the application of legal sanctions against business actors who commit breaches. The research uses a normative juridical approach, relying on statutory regulations, legal principles, and relevant literature, along with document-based analysis. The findings show that agreements made through WhatsApp can be legally binding if they meet the valid elements of a contract as stipulated in the Indonesian Civil Code (KUHPerdata). Consumers who suffer losses are entitled to protection and compensation in accordance with Article 19 of the UUPK, and business actors can be subjected to civil, administrative, or criminal sanctions if proven to have committed a breach. Transactions via WhatsApp Business fall within the scope of formal legal protection, and electronic evidence such as chats and payment proofs are legally admissible in court as guaranteed by the Electronic Information and Transactions Law (ITE Law).